2017
DOI: 10.4269/ajtmh.16-0477
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Infection in a Human Immunodeficiency Virus-1 Positive Patient Chronically Infected with Hepatitis B Virus in Western Mexico

Abstract: Abstract. Human immunodeficiency virus (HIV) and dengue coinfection has not been extensively studied. We report herein a case of dengue serotype 1 infection in an HIV-1-positive patient coinfected with hepatitis B virus (HBV) in Colima State, Mexico. CD4 + cells and HIV-1 viremia remained at normal levels, and no severe complications were observed during this multiple viral infection. The alanine transaminase and aspartate transaminase values were elevated before and during dengue infection. Surprisingly, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…These findings suggest that there was no significant HIV viral load behavior attributable to DENV infection during the study follow-up. Our results coincide with a previous report 11 in which HIV viremia remained at normal levels in a patient with a multiple HIV, DENV-1, and hepatitis B virus infection. Interestingly, a previous report suggests that HIV replication is transiently inhibited when there is a DENV-1 coinfection in peripheral blood mononuclear cells with no antiviral treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings suggest that there was no significant HIV viral load behavior attributable to DENV infection during the study follow-up. Our results coincide with a previous report 11 in which HIV viremia remained at normal levels in a patient with a multiple HIV, DENV-1, and hepatitis B virus infection. Interestingly, a previous report suggests that HIV replication is transiently inhibited when there is a DENV-1 coinfection in peripheral blood mononuclear cells with no antiviral treatment.…”
Section: Discussionsupporting
confidence: 92%
“…3,4 Nevertheless, in the case of coinfections of certain flaviviruses, such as the GB virus C (GBV-C), hepatitis C virus, or dengue virus (DENV), a reduction of the HIV-1 viral load has been observed. [5][6][7] Despite the fact that HIV infection has a worldwide distribution and that extensive regions are endemic for DENV transmission, there are only seven reports on HIV/DENV coinfection, 6,[8][9][10][11][12][13] which describe 41 patients with this simultaneous infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, other case reports reveal less favorable outcomes and even atypical presentations: a fatal pseudotumoral form of ZIKV meningoencephalitis in a heart transplant recipient has been reported (25). With respect to arbovirus infection in HIV-positive patients, data are scarce, although favorable outcomes have been reported (20,26,27). In a study of 43 HIV-positive patients with confirmed ZIKV infection, no hospitalizations, complications, or deaths were found, and CD4 cell counts and HIV viral load did not differ after ZIKV infection (28).…”
Section: Discussionmentioning
confidence: 99%